Investigating the impact of digital counseling platforms on high school students’ well-being for enhancing emotional resilience and academic performance - Hidayat, Ayi Najmul; Usanto, Usanto (Edelweiss Applied Science and Technology, 2024)
The urgency of using digital platforms in guidance and counseling services is increasing along with the need for flexible and accessible support for high school students, especially in dealing with academic pressure and emotional challenges. Digital approaches provide ease of access for students, but their effectiveness on emotional well-being and academic performance still needs to be explored. This study used qualitative methods with semi-structured interviews to explore the experiences of students who have used digital counseling platforms. Results showed that the digital platform facilitated access to counseling services and helped students manage academic stress and anxiety. Positive impacts were also seen in improved academic performance. However, the study revealed that the interpersonal relationship between counselors and students was not as strong as that established in face-to-face counseling sessions. Nonetheless, the platform offers a significant solution in supporting students’ emotional and academic well-being, especially in situations with limited face-to-face access. The results of this study emphasize the importance of developing digital counseling services that not only prioritize flexibility, but also maintain the quality of emotional connection in the counseling process.